PEPPERMINT OIL DENGAN LUKA PUTING PADA IBU MENYUSUI - Diana, Averia Eva; Maternity, Dainty; Hermawan, Dessy; Evayanti, Yulistiana (Universitas Malahayati Bandar Lampung, 2021)
Background: Pain in the nipples (nipple pain) is a problem that is often found in breastfeeding mothers and is one of the reasons why mothers choose to stop breastfeeding their babies. Data obtained at the Merbau Mataram Health Center on 10 breastfeeding mothers who had less than six months, there were 6 mothers who experienced nipple sores in the first week of breastfeeding. Purpose: This study aims to determine the effect of using peppermint oil on wounds in nursing mothers in the Merbau Mataram Public Health Center, Merbau Mataram District in 2020. Methods: This type of research is quantitative with an experimental study design. The sample in this study were 28 post partum mothers who experienced pain, and were divided into control groups and treatment groups respectively. The sampling technique used was purposive sampling technique. The research site was conducted in the work area of the UPT Mataram Merbau Health Center on June 15-July 12, 2020. The data analysis of this study used the Independent t-test. Result: The statistical test results of the Sig. (2-tailed) 0.836> 0.05, which means that Ha is rejected. The results of different tests using the Independent t-test on the mean pain scale that were placed in the control group on the fourth, eighth and 14th day were 3.29, 2.64, and 1.29, respectively, while in the treatment group were 3.21, 1.29, and 1.21. Conclusion: There is no effect of using peppermint oil on nipple wounds in breastfeeding mothers in the UPT Puskesmas Merbau Mataram Kab. Lampung Selatan in 2020. It is hoped that mothers will understand the importance of breast care since the final trimester, so that mothers can anticipate early in preventing nipple soresSuggestion It is expected for mothers to understand the importance of breast care since the final trimester, so that mothers can anticipate early in preventing nipple sores in nursing mothers. The use of a larger sample size with a more heterogeneous population needs to be done so that the research results can be generalized and to increase the validity of the research findings. Further research on breastfeeding frequency and infant sucking strength also needs to be explored in order to identify comparisons of nipple pain scales in breastfeeding mothers. Keywords : Peppermint oil, Nipple Pain Scale, Breastfeeding Technique ABSTRAK Latar belakang : Nyeri pada puting (nipple pain) merupakan masalah yang sering ditemukan pada ibu menyusui dan menjadi salah satu penyebab ibu memilih untuk berhenti menyusui bayinya. Data yang didapatkan di Puskesmas Merbau Mataram terhadap 10 ibu menyusui yang memiliki bayi kurang dari enam bulan, terdapat 6 ibu mengalami luka puting pada minggu pertama menyusui.Tujuan : Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan peppermint oil dengan luka puting pada ibu menyusui di Wilayah Kerja Puskesmas Merbau Mataram Kecamatan Merbau Mataram tahun 2020.Metode : Jenis penelitian ini merupakan kuantitatif dengan desain studi eksperimental. Sampel pada penelitian ini adalah 28 ibu post partum yang mengalami nyeri puting, dan terbagi dalam kelompok kontrol dan kelompok treatment masing-masing berjumlah 14 orang. Teknik pengambilan sampel yang digunakan adalah tekhnik purposive sampling. Tempat penelitian dilakukan di wilayah kerja UPT Puskesmas merbau Mataram pada tanggal 15 Juni-12 Juli 2020. Analisa data penelitian ini menggunakan Uji-t Independent.Hasil : Hasil uji statistik didapatkan nilai Sig. (2-tailed) 0,836 > 0,05 yang artinya Ha ditolak. Hasil Uji beda menggunakan Uji-t Independent terhadap rata-rata skala nyeri puting pada kelompok kontrol pada hari ke empat, delapan dan 14 berturut-turut adalah 3.29, 2.64, dan 1.29, sedangkan pada kelompok treatment adalah 3.21, 1.29, dan 1.21.Kesimpulan : Tidak ada pengaruh penggunaan peppermint oil dengan luka puting pada ibu menyusui di Wilayah Kerja UPT Puskesmas Merbau Mataram Kab. Lampung Selatan Tahun 2020. Diharapkan bagi ibu untuk memahami pentingnya perawatan payudara sejak trimester akhir, sehingga ibu dapat mengantisipasi lebih dini dalam mencegah terjadinya luka puttingSaran Diharapkan bagi ibu untuk memahami pentingnya perawatan payudara sejak trimester akhir, sehingga ibu dapat mengantisipasi lebih dini dalam mencegah terjadinya luka puting pada ibu menyusui. Penggunaan ukuran sampel yang lebih besar dengan populasi yang lebih heterogen perlu dilakukan agar hasil penelitian dapat digeneralisasikan dan guna meningkatkan validitas temuan penelitian. Penelitian lebih lanjut mengenai frekuensi menyusui dan kekuatan hisapan bayi juga perlu dieksplorasi guna mengidentifikasi perbandingan skala nyeri puting pada ibu menyusui.Kata Kunci : Peppermint oil, Skala Nyeri Puting, Teknik Menyusui